2017
DOI: 10.1021/acs.jafc.7b03827
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of a Novel Semi-IPN Slow-Release Fertilizer with the Function of Water Retention

Abstract: A new semi-interpenetrating polymer network (semi-IPN) slow-release fertilizer (SISRF) with water absorbency, based on the kaolin-g-poly(acrylic acid-co-acrylic amide) (kaolin-g-P(AA-co-AM)) network and linear urea-formaldehyde oligomers (UF), was prepared by solution polymerization. Nutrients phosphorus and potassium were supplied by adding dipotassium hydrogen phosphate during the preparation process. The structure and properties of SISRF were characterized by various characterization methods. SISRF showed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
(61 reference statements)
1
46
1
Order By: Relevance
“…The absorption peak of Si‐O‐Si at 1041 cm −1 in MMT was shifted to 1049 cm −1 in MMT (3%)‐SAP composite, and the absorption peak at 797 cm −1 disappeared, 22,30 which indicated that MMT was involved in the chemical reaction. In kaolin(3%)‐SAP composite, the absorption peaks at 788 cm −1 and 466 cm −1 were the stretching vibration of Si‐O‐Al and deformation vibration of Si‐O‐Si 23,31 respectively, thus, indicating that kaolin participated in the reaction. The absorption peak of APT(3%)‐SAP composite at 516 cm −1 represented the bending vibration of O‐Si‐O, 32 whereas the peak at 776 cm −1 was the deformation vibration of Si‐OH, 33 thus, indicating that APT was also involved in the reaction.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The absorption peak of Si‐O‐Si at 1041 cm −1 in MMT was shifted to 1049 cm −1 in MMT (3%)‐SAP composite, and the absorption peak at 797 cm −1 disappeared, 22,30 which indicated that MMT was involved in the chemical reaction. In kaolin(3%)‐SAP composite, the absorption peaks at 788 cm −1 and 466 cm −1 were the stretching vibration of Si‐O‐Al and deformation vibration of Si‐O‐Si 23,31 respectively, thus, indicating that kaolin participated in the reaction. The absorption peak of APT(3%)‐SAP composite at 516 cm −1 represented the bending vibration of O‐Si‐O, 32 whereas the peak at 776 cm −1 was the deformation vibration of Si‐OH, 33 thus, indicating that APT was also involved in the reaction.…”
Section: Resultsmentioning
confidence: 98%
“…20 N-hydroxymethyl acrylamide (NHA) can crosslink the polysaccharide materials with poly(acrylic acid) to form the ether groups, and the resulting SAP network composed of the ether group is generally observed to be more easily degraded than the common N, N 0 -methylene acrylamide crosslinked superabsorbent network. 21 Clay-SAP composites (such as Kaolin, MMT and APT) composite materials demonstrate low cost, expansive properties, 22 gel strength and optimal salt resistance, 23 thus, such inorganic-organic composite materials have attracted widespread attention for commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, hydrogel MSRFs can maintain soil moisture while providing nutrients for plants, 13 but resistance to degradation still exists. Xiang Y et al 14 used superabsorbent resin and urea formaldehyde to prepare a new type of MSRF through graft copolymerization and semi‐interpenetrating technology. This fertilizer has the advantages of water absorption and moisture retention and a long release period.…”
Section: Introductionmentioning
confidence: 99%
“…Such devices guarantee more effective, economical and environmentally beneficial nutrient uptake, as they prevent fertilizers from being leached from the soil [ 4 ]. Slow release fertilizer hydrogels (SRFHs) can be prepared using many different polymerization techniques, such as solution [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] or inverse suspension polymerization [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], as well as different mechanisms—free radical polymerization [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], RAFT polymerization [ 23 ], photopolymerization [ 15 , 17 , 26 ], etc. In general, there are several methods of SRFH preparation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%